LATE-AND POST-ALPINE TECTONIC EVOLUTION OF THE SOUTHERN PART OF THE ATHOS PENINSULA, NORTHERN GREECE - Georgiadis, G. Α.; Tranos, M. D.; Mountrakis, D. M. (Bulletin of the Geological Society of Greece, 2007)
The boundary between Internal Hellenides and the Hellenic hinterland is exposed in the southern part of the Athos peninsula as a NE-SW trending contact between the Serbomacedonian massif and the Circum-Rhodope Belt. The main tectonic features and deformation of the area during late- and post-alpine times have been investigated in order to understand better the late orogenic processes that led to the present arrangement of this boundary. The field study showed that the prevailing structures in the southern Athos peninsula are an asymmetric, SW-plunging, NWverging mega-scale antiform and a NE-SW striking left-lateral shear zone. These structures are the result of a transpressional deformation that initiated at least since the Eocene under ductile, syn-metamorphic (low-greenschist fades) conditions and progressively changed during the Oligocene-Early Miocene to brittle conditions with E-W striking reverse faults-thrusts and NNW-SSE striking right-lateral and NESW striking left-lateral strike-slip faults. This deformation waned in Middle Miocene changing to transtension with E- W striking, left-lateral strike-slip and NW-SE rightlateral oblique to normal faults. Since the Late Miocene an extensional regime dominates the area with the least principal stress axis (σ3) orientated NE-SW during Late Miocene - Pliocene andN-Sfrom Early Pleistocene -present